Analisis Pengaruh Leverage, Profitability, Capital Intensity Ratio Terhadap Manajemen Pajak Dengan Indikator Effective Tax Rate (Etr) Pada Perusahaan Lq45 Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2016-2018 - Murniati Murniati (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
This study aims to analyze the effect of leverage on tax management and analyze the effect of profitability on tax management and analyze the effect of capital intensity ratio on tax management. The object of this research is leverage, profitability, and capital intensity ratio on tax management. The independent variable is a variable that affects the dependent variable, either positively or negatively. The independent variables in this study are leverage, profitability, and capital intensity ratio. While the dependent variable is tax management. The results of the study indicate that the leverage variable has no significant effect on tax management, thus indicating that the level of leverage does not affect the company's tax management.